Some New Identities Related to Dedekind Sums Modulo a Prime - Jiayuan Hu (Journal of Mathematics)
The main purpose of this article is to use some identities of the classical Gauss sums, the properties of character sums, and Dedekind sums (modulo an odd prime) to study the computational problem of one-kind mean values related to Dedekind sums and give some interesting identities for them.